Pemenuhan Hak Narapidana Kelompok Rentan Lanjut Usia Pada Lembaga Pemasyarakatan - Subroto, Mitro; Setiawan, Muhammad Dhea (Innovative: Journal Of Social Science Research, 2024)
This research aims to analyze the fulfillment of the rights of elderly vulnerable group inmates in correctional institutions in Indonesia. Elderly convicts are a vulnerable group who have special needs, both in terms of health, legal protection, and treatment while serving their criminal term. However, in practice, correctional institutions in Indonesia still face various challenges in fulfilling their rights, such as overcrowding conditions, limited medical facilities, and a lack of tailored rehabilitation programs. This research uses normative research methods with a legislative approach and case studies in several prisons that have elderly prisoners. The research results show that although legal regulations in Indonesia have regulated the fulfillment of the rights of elderly prisoners, their implementation is still far from ideal. In conclusion, more comprehensive reform is needed in the correctional system, especially to ensure that the rights of elderly prisoners can be fulfilled optimally, so that they can serve their sentences with more humane and dignified treatment.